2014
DOI: 10.1007/s12275-014-4241-7
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of the bacteria responsible for pyogenic liver abscess by 16S rRNA gene pyrosequencing

Abstract: Pyogenic liver abscess (PLA) is a severe disease with considerable mortality and is often polymicrobial. Understanding the pathogens that cause PLA is the basis for PLA treatment. Here, we profiled the bacterial composition in PLA fluid by pyrosequencing the 16S ribosomal RNA (rRNA) gene based on next-generation sequencing (NGS) technology to identify etiological agents of PLA and to provide information of their 16S rRNA sequences for application to DNA-based techniques in the hospital. Twenty patients with PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…It is also well established that bacteria deriving from endogenous microbiota are common causative agents of infections in normally sterile body sites (5,6,15,23). In addition, this study and previous studies show that cultivable organisms can also be missed by routine culture (2,15).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…It is also well established that bacteria deriving from endogenous microbiota are common causative agents of infections in normally sterile body sites (5,6,15,23). In addition, this study and previous studies show that cultivable organisms can also be missed by routine culture (2,15).…”
Section: Discussionsupporting
confidence: 56%
“…We are not the first to find that molecular techniques can detect bacteria that have not been detected by culture (2) and that these additional species are not necessarily uncultivable species (15). However, studies performed to date did not include a third (and unrelated) comparator technique to further evaluate discrepancies.…”
Section: Discussionmentioning
confidence: 93%
“…Firstly, delays in sample processing have been known to increase the difficulty in identifying anaerobes through conventional culture methods [30], especially in the setting of antimicrobial therapy, which was commenced in advance of abscess drainage. Studies using pyrosequencing of direct samples have shown that pyogenic abscesses are frequently polymicrobial, with the number of aetiologic agents identified significantly exceeding what is achieved using standard culture-based methods [30, 31]. Secondly, many population-based studies accept blood cultures as an appropriate standard in diagnosing causative organisms and in guiding antimicrobial treatment in pyogenic liver abscess [32].…”
Section: Discussionmentioning
confidence: 99%
“…As a developing research area, the microbiome has been the focus of multiple studies in previous years. The non-spore-forming, anaerobic gram-negative bacterium Fusobacterium nucleatum is part of the normal flora of the human oral cavity and gut mucosa, but is an established opportunistic pathogen in periodontal diseases ( 1 4 ) and several inflammatory diseases, including inflammatory bowel disease ( 5 8 ), liver abscesses ( 9 , 10 ) and chorioamnionitis ( 11 ). Two previous studies have reported an overabundance of F. nucleatum in colorectal cancer tissues compared with adjacent normal tissues ( 12 , 13 ).…”
Section: Introductionmentioning
confidence: 99%